'Post-Olympic blues' –The diminution of celebrity in Olympic athletes. (July 2018) - Howells, Karen; Lucassen, Mathijs
Abstract: Objectives: To explore the concept of the 'post-Olympic blues' through examining the antecedents of the negative affect experienced following Olympic participation and to articulate whether the post-Olympic blues is a 'normal' short-term phenomenon or whether it is more serious and enduring. Design and method: Four female British athletes who competed in the 2016 Rio Olympic Games were interviewed and asked to draw timelines about their Olympic experiences on one or two occasions. The interviews and timelines were analyzed using Interpretative Phenomenological Analysis. Results: The athletes' experiences of the Olympic and post-Olympic period were characterized by highs around the Olympic Games and lows following their return to the United Kingdom. There were distinct temporal periods that were pertinent in the consideration of the 'post-Olympic blues'; The Olympic Experience, The Homecoming, and Moving Forwards. A fourth theme Celebrity involved integral and dynamic development over time. Celebrity comprised the development and the subsequent destruction of the athletes as celebrities. Conclusion: This study has articulated what post-Olympic blues means to those who have experienced it, identified the negative impact that the athletes' celebritization had on their mental wellbeing, and suggested that the negative emotions and subsequent behaviors were interpreted to be a normal response to returning home following Olympic participation. It is hoped that this research will engage coaching teams to formulate what support should be offered for athletes prior to and after the Olympic Games to limit the wellbeing impact that the post-Olympic blues has on athletes. Highlights: Female Olympians reported experiencing "post-Olympic blues" on return from Rio. The build up to and experiences at the Olympic Games created celebrity identities. All athletes reported negative emotions and behavioral responses on returning home. The athletes perceived a lack of formal and informal social support.